PENGARUH PELATIHAN DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KARYAWAN YANG DIMEDIASI OLEH KEPUASAN KERJA - Anisa, Arum; Susila, Ihwan (JURNAL LENTERA BISNIS, 2026)
This research employs a quantitative methodology through explanatory analysis of variables that mediate job satisfaction to assess the impact of leadership style and training on employee productivity. Data were gathered via the distribution of questionnaires to 130 employees of CV. Indonesian puspa was chosen through the purposive sampling technique. The analysis of the data was conducted utilizing SmartPLS software, employing the Partial Least Square Structural Equation Modeling (PLS-SEM) analytical approach. The findings of the research reveal that both job training and leadership style have a positive and statistically significant effect on employee productivity levels. Furthermore, job training and leadership style also exert a positive and significant influence on job satisfaction. Nevertheless, job satisfaction does not significantly affect employee productivity and fails to mediate the relationship between training and leadership style on productivity. These findings suggest that enhancements in employee productivity are more effectively attained through the direct enhancement of competencies and leadership attributes rather than through emotional factors such as job satisfaction. It is anticipated that this research will serve as a foundational reference for organizations in formulating HR development strategies that are more focused on boosting productivity.